Keanekaragaman Jenis Landak Laut Kelas Echinoidea di Pantai Kadahang Kabupaten Sumba Timur - Susani Rambu Anahau; Anita Tamu Ina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The purpose of this study was to determine the diversity of sea urchin species on the Kadahang Beach, East Sumba Regency. The sampling technique used is a purposive sampling and analyzed using a quantitative descriptive approach with the Shannon-Wiener diversity index formula. Sea urchin samples were calculated using the quadratic transect technique with a plot size of 1 x 1 meter placed perpendicular to the inside of 50 meters using a plot of 16 plots. The environmental factors measured were temperature, salinity, and acidity (pH). Measurements were carried out at two observation stations. The results showed that 8 species of sea urchin were divided into 4 orders, namely the orders Echinaceae, Diadematoida, Camarodonta, and Stomopnestes. The diversity index obtained is in the moderate category with a value of H` = 2.026.